IMPLEMENTASI KANVAS DIGITAL DALAM PEMBELAJARAN SENI RUPA UNTUK MENINGKATKAN MINAT DAN KREATIVITAS SISWA KELAS VII SMP NEGERI 8 SEMARANG - Septianingtyas, Monik; Ayu Pratiwinindya, Ratih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Visual arts education at the junior high school level still tends to rely on conventional media, so the use of digital technology in the creative process has not yet been optimized. In fact, the use of digital media has the potential to enhance student learning and creativity. This study aims to describe the implementation of digital canvas through the IbisPaint X application and to analyze the increase in student participation and its impact on creativity and the quality of artwork in illustration drawing lessons in Grade 7 at SMP N 8 Semarang. This study employs a descriptive qualitative approach using observation, interviews, and documentation of the art teacher as well as students in Grade 7E and 7H. Data were analyzed through reduction, presentation, and drawing of conclusions, and their validity was tested using triangulation of methods. The results of the study indicate that the use of digital canvases encourages more active student engagement and improves the quality of artwork, as evidenced by improvements in line work, composition, and color application. Additionally, digital features such as undo and layers simplify the creative process, encouraging students to explore more boldly. Technical challenges encountered in the early stages can be addressed through teacher guidance and an adaptation process. Thus, the IbisPaint X-based digital canvas is effective as an innovative medium in visual arts education.